(untitled) (Orthodontic Journal of Nepal, 2022)
Introduction: Age estimation is an important parameter in forensic for identification of individuals. Cameriere developed pulp tooth area ratio as age estimation method in Orthopantomogram. Objective of this study was to use Pulp tooth area ratio of mandibular premolars and derive population-specific equations for age estimation. Materials and Method: A retrospective study was conducted in Department of Oral and Maxillofacial Pathology, Kantipur Dental College and Teaching Hospital from June 2021 to November 2021 after ethical clearance no 10/021. Total 392, Orthopantomograms of patients aged 17- 50 years with mandibular premolars were retrieved from Department of Oral Medicine and Radiology. The radiographic images were saved as JPEG file and images of premolars were processed using Image J software. Pulp and tooth area were measured and their ratio was calculated. Result: There were 178 males and 214 females with mean age of 22.39 years. Paired T tests showed good intra observer agreement between mandibular premolars. In our study pulp tooth area ratio ranged from 0.0109 to 0.2307 for 45, 0.0456 to 0.2030 for 44, 0.0413 to 0.2239 for 35 and 0.0639 to 0.2204 for 34. Linear regression analysis generated several formulae for all mandibular premolars which was statistically significant. Derived equations were used to test for accuracy in the 40 new samples which showed mean accuracy error between 5.65 to 6.40 years. Conclusion: Derived equations from Pulp tooth area ratio of mandibular premolars can be used for age estimation in young adults from Nepalese population sample.